Inter-scalar and inter-disciplinary approaches for a valley community. The case of Sappada (EAAE Annual Conference Proceedings, 2023)
Our research aimed to explore an inter-scalar field in which architectural design tools are intertwined with urban and territorial scales. The case is an enclave between different limits: a valley near the border with Austria, located on the edge of north of Veneto region with an ethnic-linguistic heritage of Germanic matrix, administratively migrated in 2017 to Friuli Venezia Giulia region.